Study on anthocyanins from Lycium ruthenicum Murr via ultrasonic microwave synergistic extraction and its antioxidant properties - Dong, Yuhe; Zhong, Wenting; Yang, Chunmiao; Zhang, Yongze; Yang, Dongsheng (Frontiers in Sustainable Food Systems, 2022)
The objectives of this study are to optimize the ultrasonic microwave synergistic extraction (UMSE) of anthocyanins from Lycium ruthenicum Murr (ALRM) by response surface methodology and also to investigate its antioxidant activity in vitro. Based on the single-factor experiments, we optimized the ALRM extraction process by response surface methodology assuming anthocyanin extraction rate as the response point and microwave power, ultrasonic power, extraction time, and liquid-to-material ratio as the investigating parameters as well as performed correlation analysis between DPPH·, ·OH, ABTS·, O2ˉ· radical scavenging potential, and ferric-reducing antioxidant power. The results showed that the influence on anthocyanin yield was in the order of liquid to material ratio > microwave power > ultrasonic power > extraction time; the elicited extraction conditions were: ultrasonic power 216.253 W, microwave power 89.311 W, time 26.141 min, liquid to material ratio 17.294 mL/g, the forecast content was 10.157 mg/g, while the actual value was consistent with the preview value. Meanwhile, ALRM obtainable by UMSE was identified as yielding favourable antioxidant properties firstly, when the concentration of purified ALRM (ALRM-1) was increased, the antioxidant capacity was strengthened. Theoretically, we provide a basis for the extraction procedure of ALRM and its antioxidant activity, which serves as a promising antioxidant and free radical scavenger.